Fat-1 Transgenic Mice With Augmented n3-Polyunsaturated Fatty Acids Are Protected From Liver Injury Caused by Acute-On-Chronic Ethanol Administration - Warner, Jeffrey; Hardesty, Josiah; Song, Ying; Sun, Rui; Deng, Zhongbin; Xu, Raobo; Yin, Xinmin; Zhang, Xiang; McClain, Craig; Warner, Dennis; Kirpich, Irina (Frontiers in Pharmacology, 2021)
Alcohol-associated liver disease (ALD) is the leading cause of liver disease worldwide, and alcohol-associated hepatitis (AH), a severe form of ALD, is a major contributor to the mortality and morbidity due to ALD. Many factors modulate susceptibility to ALD development and progression, including nutritional factors such as dietary fatty acids. Recent work from our group and others showed that modulation of dietary or endogenous levels of n6- and n3-polyunsaturated fatty acids (PUFAs) can exacerbate or attenuate experimental ALD, respectively. In the current study, we interrogated the effects of endogenous n3-PUFA enrichment in a mouse model which recapitulates features of early human AH using transgenic fat-1 mice which endogenously convert n6-PUFAs to n3-PUFAs. Male wild type (WT) and fat-1 littermates were provided an ethanol (EtOH, 5% v/v)-containing liquid diet for 10 days, then administered a binge of EtOH (5 g/kg) by oral gavage on the 11th day, 9 hours prior to sacrifice. In WT mice, EtOH treatment resulted in liver injury as determined by significantly elevated plasma ALT levels, whereas in fat-1 mice, EtOH caused no increase in this biomarker. Compared to their pair-fed controls, a significant EtOH-mediated increase in liver neutrophil infiltration was observed also in WT, but not fat-1 mice. The hepatic expression of several cytokines and chemokines, including Pai-1, was significantly lower in fat-1 vs. WT EtOH-challenged mice. Cultured bone marrow-derived macrophages isolated from fat-1 mice expressed less Pai-1 and Cxcl2 (a canonical neutrophil chemoattractant) mRNA compared to WT when stimulated with lipopolysaccharide. Further, we observed decreased pro-inflammatory M1 liver tissue-resident macrophages (Kupffer cells, KCs), as well as increased liver T regulatory cells in fat-1 vs. WT EtOH-fed mice. Taken together, our data demonstrated protective effects of endogenous n3-PUFA enrichment on liver injury caused by an acute-on-chronic EtOH exposure, a paradigm which recapitulates human AH, suggesting that n3-PUFAs may be a viable nutritional adjuvant therapy for this disease.